Communications Security Research on "Man-in-the-Loop" Television Guidance System Data Link - Sun, Chao; Liu, Yukun; Jiang, Shouda (IIH-MSP 2008 : 2008 Fourth International Conference on Intelligent Information Hiding and Multimedia Signal Processing : 15-17 August 2008, Harbin, China, 2008)
This paper aims at the correspondence hidden dangerous problem in "man-in-the-loop" television guidance system data link, proposed a secure communication protocol base on general analysis of the principle and characteristic of current many kinds of cipher systems, which may apply in the "man-inthe-loop" television guidance data link. And the security and real time analysis of the proposed protocol has been carried out as well.